Functional health literacy: protective role in adherence to treatment for hypertensive patients - Luciana Ricarte Cavalcante; Luciara Leite Brito; Helena Fraga-Maia (Universidade de Fortaleza, 2020)
Objective: To investigate factors associated with Functional Health Literacy (FHL), as well as its role as a probable protective factor for treatment adherence in individuals with hypertension (SAH), attended in Primary Health Care (Atenção Primária à Saúde - APS) units. Methods: This is a cross-sectional study with APS users under antihypertensive medication in the city of Salvador, Bahia. Illiterate or functionally illiterate patients were excluded, as well as those with a history of ischemic stroke. Data were collected between November 2015 and August 2016. Sociodemographic and clinical data were accessed utilizing a structured instrument developed by the authors, and the FHL was assessed using the REALM. Descriptive analyses and logistic regression were performed. Results: The population comprised 286 individuals and it was observed that low schooling was associated with inadequate FHL, both in the gross and adjusted analysis (OR = 9.25; CI95%: 4.49 - 19.05) and with the professional activity of manual labor (OR = 9.90; CI95%: 2.08 - 46.90). In patients with schooling levels of over 8 years, it was observed that the FHL was significantly associated with non-adherence to medical treatment, even after adjustment by gender, age, civil status, physical activity, and skin color (OR = 3.0; CI95%: 1.2 - 7.9). Conclusions: Inadequate FHL was significantly associated with non-adhesion to treatment only for those with over 8 years of schooling. Improvements in health promotion actions should be reinforced to address chronic diseases such as SAH.